Two times two temperaments of legal scholarship and the question of commodification. Issue 3 (September 2022) - Somek, Alexander
Abstract: The article offers a brief account of the continental European (viz., German) and the US American approach to legal education and scholarship. It then explores in which respect legal academics active in these cultures are vulnerable to the lure of commodification, that is, incentives to produce legal expertise for clients. After concluding that these incentives may well be stronger in countries where legal academics consider themselves badly paid and where scholarly traditions are weak, the article explores how commodification can adversely affect the culture of 'legal science' as a whole and even work to the detriment of clients.